2017
DOI: 10.2151/sola.2017-038
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Predictability of the North Atlantic Oscillation and Zonal Mean Fields Associated with Stratospheric Influence in JMA/MRI-CPS2

Abstract: The North Atlantic Oscillation (NAO) is the most dominant hemispheric variability affecting the winter climate. It is, however, difficult to predict the NAO on a seasonal time scale. Thus, a better understanding of the NAO is important for improving the accuracy of seasonal forecasts. We investigated the seasonal predictability of the NAO and the zonal mean fields of the stratosphere using hindcasts based on the operational seasonal prediction system of the Japan Meteorological Agency. We found that both the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This implies predictability of European and North American winter climate out to a season or even longer ahead. 20,[22][23][24][25][26][27][28][29] All of these studies use ensembles and create an ensemble mean model prediction M to reduce the level of unpredictable noise:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies predictability of European and North American winter climate out to a season or even longer ahead. 20,[22][23][24][25][26][27][28][29] All of these studies use ensembles and create an ensemble mean model prediction M to reduce the level of unpredictable noise:…”
Section: Introductionmentioning
confidence: 99%
“…RPC values above 1 were not generally expected, but this second possibility has been considered 32 and examples have now been found in a number of different ensemble seasonal predictions, particularly in winter predictions of the NAO and Arctic Oscillation. 21,23,25,28,29 For example, in the seasonal forecasts of the NAO reported by Scaife et al, 23 the predictable ensemble mean signal was around 2 hPa, the total ensemble variability was around 8 hPa and the correlation was around 0.6 so the RPC = 0.6/(2./8.) > 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies further showed that if a dynamical prediction system is capable of capturing the relation of the winter AO to the sea ice, SST and snow cover, it can predict a portion of the AO's variability (Riddle et al, 2013;Scaife et al, 2014;Sun and Ahn, 2015). Furthermore, some other researches demonstrated that the stratosphere is also one of the sources of the predictability and contributes to the enhancement of the predictive skill of the AO/North Atlantic Oscillation (NAO) in winter (Sigmond et al, 2013;Scaife et al, 2014;Scaife et al, 2016;Saito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on NAO seasonal prediction [21][22][23][24][25]. Saito et al [26] found that the predictive skill of the NAO increases from late winter to early spring in relation to the high predictability of the zonal mean geopotential height in the stratosphere. The year-to-year increment method has shown advantages in predictions of the winter NAO [21,27].…”
Section: Introductionmentioning
confidence: 99%